2014
DOI: 10.1002/app.41270
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of making PVF porous foam without using the pore forming agent

Abstract: Different with the conventional method of manufacturing poly(vinyl formal) (PVF) porous foam by using the pore‐forming agents such as wheat or potato starches, a novel method without using the pore‐forming agent is introduced in this article. Through the help of images taken by a scanning electron microscope, the formation process of the present PVF foam will be discussed in terms of the spinodal decomposition (SD) phase separation principle. Additionally, the effect of poly(vinyl alcohol) concentration and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Figure shows that the pore size increases with increasing formaldehyde dosage. Chang reported that decreasing the PVA reactant solid contents is a major cause of pore size increase . The effect of formaldehyde dosage on PVF foam pore sizes prepared using PVA‐0588 is the opposite of that using PVA‐1799.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows that the pore size increases with increasing formaldehyde dosage. Chang reported that decreasing the PVA reactant solid contents is a major cause of pore size increase . The effect of formaldehyde dosage on PVF foam pore sizes prepared using PVA‐0588 is the opposite of that using PVA‐1799.…”
Section: Resultsmentioning
confidence: 99%
“…Because of hydroxyl activity, PVA with a high degree of polymerization is easier to react with aldehydes. The high acetal products obtained with formaldehyde are usually poly(vinyl formal) (PVF) foams with open‐cell structure . By introducing different foaming methods, PVF with different pore sizes (more than 20 µm) can be prepared .…”
Section: Introductionmentioning
confidence: 99%
“…Commercial polyvinyl alcohol (BF-17) with averaged polymerization degree of 1700 and hydrolysis degree of 98.5-99.2 mol % were obtained from Chang-Chun Petrochemical Co., Ltd, Taiwan [8].…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Polyvinyl alcohol foam (PVAF) is synthesized with polyvinyl alcohol (PVA) and formaldehyde [8][9][10][11][12][13][14]. A novel polyvinyl alcohol foam (PVAF) with fully open cells and channels was designed by using a super clean bioimmic airfoaming process [8][9][10][11][12][13][14].…”
Section: Preparation Of Polyvinyl Alcohol Foam (Pvaf) By Using Two Traditional Foaming Process and A Super Clean Bioimmic Air-foaming Promentioning
confidence: 99%
See 1 more Smart Citation